2013
DOI: 10.1016/j.jbi.2013.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Interestingness measures and strategies for mining multi-ontology multi-level association rules from gene ontology annotations for the discovery of new GO relationships

Abstract: The Gene Ontology (GO), a set of three sub-ontologies, is one of the most popular bio-ontologies used for describing gene product characteristics. GO annotation data containing terms from multiple sub-ontologies and at different levels in the ontologies is an important source of implicit relationships between terms from the three sub-ontologies. Data mining techniques such as association rule mining that are tailored to mine from multiple ontologies at multiple levels of abstraction are required for effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…The approach consists in combining data mining and statistical measurement techniques (such as redundancy analysis, sampling and multivariate statistical analysis) to discard the insignificant rules. Alcala-Fdez et al proposed a method based on rule covers to prune ARs [4]. The method defines subsets of rules describing the same transaction row.…”
Section: Objective and Subjective Methods For Ar's Post-processingmentioning
confidence: 99%
“…The approach consists in combining data mining and statistical measurement techniques (such as redundancy analysis, sampling and multivariate statistical analysis) to discard the insignificant rules. Alcala-Fdez et al proposed a method based on rule covers to prune ARs [4]. The method defines subsets of rules describing the same transaction row.…”
Section: Objective and Subjective Methods For Ar's Post-processingmentioning
confidence: 99%
“…Another approach where ARL from GO is used, is the work of Manda et al [15]. The methodology developed by Manda et al is based on a new algorithm called Multiontology data mining at All Levels (MOAL).…”
Section: Related Workmentioning
confidence: 99%
“…They applied this method to a medical domain dataset, and through this means they demonstrated that the hybrid method provided a mechanism for reusing and automatically updating a knowledge base. The MOAL: Multi-Ontology data mining at All Levels algorithm [19] uses the structure and relationships of a Genetic Ontology to mine multi-ontology multi-level association rules. They introduce two interestingness measures: Multi-ontology support and Multi-ontology confidence customized to evaluate multi-ontology multilevel association rules.…”
Section: Related Workmentioning
confidence: 99%